Green Human Resource Management: Policies and practices - Shoeb Ahmad; Tahir Nisar (Cogent Business & Management, 2015)
Recently, there has been observed an increasing awareness within business communities on the significance of going green and adopting various environment management techniques. As the corporate world is going global, the business is experiencing a shift from a conventional financial structure to a modern capacity-based economy which is ready to explore green economic facets of business. Today, Green Human Resource Management (GHRM) has become a key business strategy for the significant organizations where Human Resource Departments play an active part in going green at the office. The paper largely focuses upon the various Green Human Resource Practices pursued by the organizations all over the world and, explains the simplified meaning of GHRM. The study also adds to the extant literature by discussing future direction of some GHRM functions. Finally, the paper suggests some potentially prolific HR initiatives for Green organizations.
Keywords: 650